Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model PBL di Kelas IV SD - Wulandari, Vina; Eliyasni, Rifda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This research was aimed to describe the improvement of learning process through Problem Based Learning (PBL) model at grade IV of SDN 36 Cengkeh in Padang City. Based on the observation, it was found that the teachers did not guide teaching based on problem-oriented, they did not organize the learners to learn, they did not guide the learners independently or in groups, they did not make the learners develop nor present the results of their work, they did not involve the learners in analyzing and evaluating the results of problem solving. The design of the research was classroom action research through qualitative and quantitative approaches. The subjects of this research were the teachers and the learners. The results of this research showed that there are some improvements; the average value is 86.66% at the first cycle of Lesson Plan (RPP). It increases to 96.66% in the second cycle. The observation of the integrated thematic learning process in the first cycle is 78.56% and it increases in the second cycle to 95.23%. The average assessment is 80% for both teacher and students aspects in the first cycle. It increases to 95% in the second cycle.